Local wisdom on a Short Story of Works by Students of Class XI SMA Negeri 19 Medan TP 2021/2022 - Elvi Yulianti (CV. AFDIFAL MAJU BERKAH, 2022)
This research discusses about the local wisdom on a short story of works by students of class XI of the type of local wisdom, how to penyaajian local wisdom, and the motives of local wisdom. This research uses qualitative method with descriptive analysis, narrative analysis with the model Aktan Greimas. The Data in the form of writing short stories of the students and an interview. The results of the research in the form of the type of local knowledge of the environment of the students, the presentation of the local wisdom of many of the dialog antartokoh, and students ' motivation to introduce the traditions and culture